Problems of Vaccinal Prevention in Adult Population - N. I. Briko; N. N. Tsapkova; L. R. Batyrshina; V. A. Korshunov; I. V. Feldblyum; A. V. Bikmieva; K. A. Subbotina; O. V. Filippov (Эпидемиология и вакцинопрофилактика)
The analysis of the vaccine preventive status of infectious diseases in adults in Russia and various countries of the world is presented in the  article. The problems and directions of improving the immunization of the adult population in Russia are identified.